“Angkatan Korona”: Stigma Terhadap Lulusan SMA Angkatan 2020 - Ratmanda Ratmanda (Emik, 2022)
The pandemic Covid-19, which has spread throughout the world including Indonesia, has had a major impact on various aspects of life, including in the field of education. While the existing literatures are more related to stigma on people infected with Covid-19 and on the health workers who care for them, this article is deals with stigma against 2020 high school graduates and those who enrolled college in the same year, and they are labeled "angkatan korona". Using this qualitative approach, this study was carried out through social media, such as Whatsapp, Facebook, Instagram, and Twitter. Data was collected using in-depth interview and observation methods. While interviews were conducted using Whatsapp, Instagram, Twitter application, then the observation was carried out using the Whatsapp, Facebook, Instagram, and Twitter applications by observing posts related to the "angkatan korona". Those who participated in this study were 11 people, consisting of three boys and eight girls; who’s aged between 18 and 20 years and came from five different universities. The results of this study indicate that the "angkatan korona" is a stigma aimed at 2020 high school graduates. Stigma against the “angkatan korona” not only happened in cyberspace, but also in the real world. While stigma in cyberspace is carried out through postings on social media, then stigma in the real world is carried out directly. This stigma is caused by the abolition of the National Examination (Ujian Nasional) and graduation celebrations, the online learning system and communication among students only through social media (online friendships). It is argued in this article that government policies during the Covid-19 pandemic have created stigma against people who have been impacted on these policies.